The Relationship Between Sleep Quality and Constipation in Patients with Chronic Kidney Disease (CKD) - Yully Yanti Fadillah; Ribka S Panjaitan; Rizqa Wahdini (Jurnal Keperawatan Profesional, 2026)
Chronic kidney disease (CKD) is a progressive condition that affects the body's systemic balance, including digestive function and sleep quality. Constipation and poor sleep quality often occur concurrently; however, local studies highlighting their association remain limited. The primary objective of this study is to examine the relationship between sleep quality and constipation in patients with chronic kidney disease (CKD). This research employed a quantitative method with a cross-sectional approach. A total of 93 chronic kidney disease (CKD) patients were selected using purposive sampling. Instruments used to assess sleep quality included the Pittsburgh Sleep Quality Index (PSQI), while constipation symptoms were evaluated using the Patient Assessment of Constipation Symptoms (PAC-SYM) questionnaire. Data analysis was conducted using univariate and bivariate approaches, with the chi-square test applied for statistical significance. The results showed that the majority of patients experienced poor sleep quality (84.9%) and constipation symptoms (53.8%). The chi-square test yielded a p-value <0.001, indicating a significant association between sleep quality and constipation. Poor sleep quality was significantly correlated with an increased incidence of constipation among CKD patients. These findings support the importance of a holistic approach in nursing care, emphasizing sleep quality as a potential risk factor for constipation.